Superimposed macro- and mesoscale folds, and their relation to ductile shear zones in the Karasjok Greenstone Belt, Finnmark, Norway - Stokmo, Eirik Bache (UiT Norges arktiske universitet, 2020)
The Karasjok Greenstone Belt (KGB) is a N-S trending supracrustal belt in Northern Norway. The KGB may comprise economically important mineral resources. Thus, a better understanding of ore genesis and structural architecture is key information for future exploration. The purpose of this master thesis is to perform detailed structural analysis based on field work in the northern part of KGB. Field data will be combined with exsiting geological data and integrated with high-resolution ortho-photos and aeromagnetic data from Lakselv. This will be used as a basis for interpreting the structural architecture in more detail and to compare it with other areas of the KGB. The present work shows that the stratigraphic sequence is partly inverted. This is likely due to macro-scale overturned folding and possible imbrication. A detailed study of F1 and F2 folds show Ramsey type 2 interference fold patterns. The type 2 pattern suggests NW directed folding and imbricate shearing which is partly in contrast with previous D1 deformation models. The D1 deformation event is followed by strongly asymmetric SW vergent D2 shear folding. Finally, small scale ductile D3 shear zones produced moderately plunging drag folds and fault-propagation folds. The D1 and D3 events in the Lakselv area are not evident farther south in the KGB. Here, the magnetic data mostly show linear NW-SE striking anomalies. This might correspond to D2 structural trends seen in Lakselv. The southernmost part of the KGB shows an anomaly pattern that resembles the refolded pattern in Lakselv. The proposed new D1 model with imbricate folding and associated local inversion may correspond with structures in the northeastern parts of the Kautokeino Greenstone Belt, the Repparfjorden Tectonic Window, and magnetic anomalies within the Jergul Gneiss Complex. The relative timing of the deformation as well as the tectonic evolution correspond with both Svecofennian- and Lapland-Kola deformation. Further work is needed to confirm that the D1 phase within the study area ...